1999
DOI: 10.1038/sj.ejcn.1600779
|View full text |Cite
|
Sign up to set email alerts
|

Diets high and low in glycemic index versus high monounsaturated fat diets: effects on glucose and lipid metabolism in NIDDM

Abstract: Objective: To examine the relative effects of high and low glycemic index (GI) carbohydrates, and monounsaturated fats on blood glucose and lipid metabolism in NIDDM subjects. Subjects: Fourteen male and seven female variably controlled NIDDM subjects recruited by advertisement. Setting: Free living outpatients. Research design: A repeated measures, within-subject design was used such that each subject consumed three diets: (a) a high-GI diet (53% CHO7 21% fat, 63 GI units (glucose 100)); (b) a low-GI diet (51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 36 publications
5
108
1
Order By: Relevance
“…Since recent studies have indicated that the glycemic index of foods is positively associated with the risk of developing type 2 diabetes (Salmeron et al, 1997a,b) and that low GI diets may reduce glycemia and cardiovascular risk factors in diabetes (Järvi et al, 1999;Fontvieille et al, 1999;Luscombe et al, 1999), development of palatable, low GI or functional foods has become increasingly important. This study shows that each gram of bglucan can be expected to lower the GI of a food by four GI units and that this effect is not attenuated by processing, including the use of fructose to enhance palatability.…”
Section: Discussionmentioning
confidence: 99%
“…Since recent studies have indicated that the glycemic index of foods is positively associated with the risk of developing type 2 diabetes (Salmeron et al, 1997a,b) and that low GI diets may reduce glycemia and cardiovascular risk factors in diabetes (Järvi et al, 1999;Fontvieille et al, 1999;Luscombe et al, 1999), development of palatable, low GI or functional foods has become increasingly important. This study shows that each gram of bglucan can be expected to lower the GI of a food by four GI units and that this effect is not attenuated by processing, including the use of fructose to enhance palatability.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all carbohydrate-rich diets may produce the same effects on HDL levels, as low-GI diets may confer a more favorable lipid profile compared with high-GI diets. Lowering the dietary GI by at least 12 points reduced triglycerides by approximately 9% in 10 out of 11 studies (Brand Miller, 1994) and recent data showed that a high carbohydrate diet made of low-GI foods significantly increased HDL levels by 5.4% compared to an isocaloric high carbohydrate=high GI diet (Luscombe et al, 1999). In addition, cross-sectional data (Frost et al, 1999;Ford & Liu, 2001) showed that dietary GI was inversely related to HDL cholesterol levels, which in turn were inversely related to triglycerides, and that GI was a stronger predictor of serum HDL levels than dietary fat (Frost et al, 1999).…”
Section: The Glycemic Index In Coronary Heart Diseasementioning
confidence: 99%
“…On the other hand, Jenkins proposed the glycemic index (GI) as a physiologic basis for qualitative classification of carbohydrate-containing foods, where low GI foods produce less glycemia than high GI foods (Jenkins et al, 1981). Since then, many metabolic studies showed that a low GI diet improves overall blood glucose and lipid profiles in normal subjects (Jenkins et al, 1987a), and patients with hyperlipidemia (Jenkins et al, 1985(Jenkins et al, ,1987b or diabetes (Jenkins et al, 1988;Brand et al, 1991;Wolever et al, 1992a, b;Jarvi et al, 1999;Luscombe et al, 1999). The GI values of 565 foods were compiled to form the international GI table in 1995.…”
Section: Introductionmentioning
confidence: 99%